Parental views from rural Cambodia on disability causation and change - Morgan, F.; Tan, Boon (Informa Healthcare, 2011)
Purpose. This study explored the beliefs of Cambodian parents of children with cerebral palsy regarding disability causation and their perceptions of the effectiveness of interventions in bringing about change in their child. Results. Beliefs around disability causation were mixed, with equal numbers of participants attributing their child's disability to biomedical causes as to traditional causes incorporating elements of Theravada Buddhism, animism and Brahmanism. While many participants had initially sought traditional interventions for their child, few found them to be effective and most had subsequently utilised medical and rehabilitation services. Parents whose children were moderately or severely impaired perceived both traditional interventions and rehabilitation to be less effective than parents of children with mild impairments. Participants generally judged the effectiveness of interventions based on functional changes in their child. Conclusions. The complexity of Khmer belief systems was reflected in the range of participants' perceptions of the cause of their child's disability, yet beliefs around disability causation did not appear to have determined their care-seeking behaviour or their perceptions of effectiveness of interventions.